Fine Art education in Great Britain and Ireland with particular reference to the influence of modernism on the curriculum of the National College of Art and Design, 1977-1988 - O'Neill, Peter (Trinity College (Dublin, Ireland). School of Education, 2002)
In 1975 a major change was brought about in the curriculum in the Fine Art faculty at The National College of Art and Design in Dublin. The introduction of this curriculum followed a period of unrest at the college. This unrest was a direct consequence of major social changes that had taken place in Ireland throughout the 1960s. These changes saw Ireland shed the isolationist political philosophy of the new state that had followed independence and adopt a new outward looking philosophy. The principal effect of this change at the college in Dublin in the 1960s was a rebellion by students against what they perceived, in the light of the above changes, as an outmoded curriculum. The values of the curriculum that students rejected were rooted in the neo-classical curricula of the eighteenth century academies of art and the nationalist political ideology of post-independent Ireland. The values that students espoused were those of modernism. Following the student rebellion a new structure was introduced at the school of art in Dublin. This structure was modeled on the system of art education that had been developed in Britain in the 1960s in the context of the rapid expansion of the British education system at that time. Fine art education in Britain as it developed at this time owed much to the reformative aspect of developments that took place in British society and education after the Second World War and in particular to the influence of the so-called Coldstream Report of 1960.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin